From Cardiovascular Prevention and Differential Diagnosis to the Treatment of Myocardial Damage-Experimental and Human Perspectives - Pitha, Jan (International journal of molecular sciences, 2023)
Cardiovascular diseases are characterized by many clinical, morphological, functional, and biochemical markers, including age, sex, genetic factors, plasma lipids, glycemia, and many other laboratory parameters [...].
Keywords: Diagnosis, Differential; kardiovaskulární nemoci; diferenciální diagnóza; lidé; Myocardium; biologické markery; myokard; Cardiovascular Diseases; Biomarkers; Humans